EgNa 2.0 / Hakimi Hafiz Hasbullah ... [et al.] - Hasbullah, Hakimi Hafiz; Efendi, Malik; Mohammad Hisham, Muhammad Haziq; Mohamad, Nurul Ashikin (2020)
Eggs shells and banana skins are the domestic waste used to produce these organic fertilizers. It's effective. One innovation in organic fertilizer production. Can improve the economy of the local community. Reducing dependence on chemicals in the market. EgNa Fertilizer also serves as organic fertilizer and can solve local problems with dermal shell debris. This innovation can prove the effectiveness of egg shells to help tree growth. This product is environmentally friendly, easy & save and safer. The results of the experiments were neutral pH value and the tree became more fertile when added to the egg husk. Among the products contributed to reducing the number of dead plants caused by chemical fertilizers. Furthermore, it also improves the local economy and optimizes the use of egg shells and reduces pollution. No other fertilizers use the egg shell as the main ingredient. Easy to use. Saves natural resources. Improve the economy of the locals. Reduces the problem of dumping eggshells. This product has the opportunity to be marketed because the raw material is natural and it is profitable. Profit is expected as early as the first quarter of marketing. This product is very attractive to buyers, especially nature lovers. Its use is devoted to the agricultural industry. Target groups are farmers and growers. Method of production, Sifted egg shells to get the powder. Eggplant eggs are mixed with stripped bananas skin. Eggplant eggs are mixed with stripped bananas skin. Experimental results show that EgNa is very effective in helping tree seedlings, neutral, safe and portable. In conclusion, EgNa Fertilizer is the best product to solve the environment problem.